Parâmetros físico-químicos de estrelas com planetas na missão CoRoT - Correia, Caio Fábio Teixeira (2011)
In the present study we compute the atmospheric parameters (Teff , log g and vmic, [Fe/H]) and chemical abundance of 16 ions (Fe I, Fe II, O I, Si I, Na I, Mg I, Al I, Ca I, Ti I, Co I, Ni I, Rb I, Zr I, Ba II, La II and Cr I) for 16 solar-like stars with masses between 0:8 and 1:2 Mfi aproximatedly, including 10 planet-host stars detected by the CoRoT Space Mission. For this study, we use data from the ESO public archive: (i) high resolution spectra (R 47000) from the UVES spectrograph on the VLT/UT2-ESO (for 7 stars, covering the wavelength range 3450-4515 Å and 5500-9400 Å) and (ii) high resolution spectra from HARPS spectrograph on the La Silla-ESO 3.60 m telescope (for 9 stars, covering the wavelength range 4200-6865 Å). Our spectral analysis is based on MARCS models of atmosphere and Turbospectrum spectroscopic tools. On the base of the computed parameters, the referred abundances appears to follow the same behavior of the solar curve abundances. Further, one observes a signifficant correlation between the abundance ratio [m/Fe] and condensation temperature (Tc) of refractory elements (Tc > 900 K). The behavior of the projected rotational velocity (v sin i) versus the computed abundances [m/Fe] is also analyzed, presenting no clear trends. This study oers additional constraints to trace the evolutive history of solar-like stars with planets, including the search for chemical dierences between stars with and without transit planets and anomalies in the studied abundances